(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the diagnostic accuracy of plasma D-Dimer levels in clinically suspected patients of pulmonary embolism (PE) taking computed tomography pulmonary angiography (CTPA) as gold standard. Study Design: Descriptive Cross sectional study Place and Duration of Study: This study was conducted at the In Sahiwal Teaching Hospital in collaboration of Pathology and Radiology Departments of Sahiwal Teaching Hospital from 15th June ,2022 – 14th December, 2022. Materials and Methods: We enrolled 50 subjects of suspected pulmonary embolism based on clinical signs and symptoms e.g. chest pain and shortness of breath. Their D-dimer levels and CTPA were done. Data was analyzed using SPSS version 23.0. Descriptive statistics were applied. Degree of association was also analyzed between Plasma D-dimer levels and pulmonary thromboembolism on CTPA by applying chi-square test. The p-value ≤0.05 was considered as statistically significant. Sensitivity, specificity, positive predictive value and negative predictive value of Plasma D-dimer levels in pulmonary thromboembolism were calculated taking CT pulmonary angiography as gold standard. Association was also analyzed between pulmonary thromboembolism on CTPA and other findings noted on HRCT chest images. Results: Among 50 included subjects, 58 % were males and 42 % were females with mean age of 49.5 + 7.55. D-Dimers were found to be elevated (> 500 ng/ml) in 44% of cases. Pulmonary thromboembolism was seen by CTPA in 54 % of cases. While in 46 % of cases, PE was not detected. Statically significant association was seen between collapse/consolidation and presence of pulmonary thromboembolism (p-value 0.0001) on CTPA. D-dimers were found to be significantly higher in patients with pulmonary thromboembolism (p-value 0.024). The sensitivity, specificity, positive predictive value (PPV) , negative predictive value(NPV) and diagnostic accuracy of D-dimer levels in predicting existence of thromboembolism were 59.2 % , 73.9 % , 72.8 % , 60.7 % and 66.0 % respectively. Conclusion: Although D-Dimer levels exhibits low sensitivity and specificity to diagnose pulmonary embolism, it is helpful for initial workup of the disease. However, CTPA stands as gold standard modality for definitive diagnosis of Pulmonary Embolism.